The Digital and Paper Maps as Substitute Goods Offers on Electronic Auction Platform - Dariusz GRABARA (Communications of International Proceedings, 2021)
Paper maps, and with the advent of digital services also digital maps, made trips effortless to accomplish. However, paper maps and their digital counterparts, remain substitutable goods. The study assessed the number of auctions in substitute map categories and explored the utilization of auction vignette factors. The study comprised 5.407 offers of digital maps, and 23.596 offers of paper maps. The digital maps were offered at the significantly lower rate of 1 to 4.36 than their paper counterparts. Utilization of share of auction vignette factors showed that digital maps leaded in offers with factors like “Second price” (4.59:1), “Featured” (14.18:1), “Allegro Coins” (2.10:1), and “Free shipping” (2.84:1) options, while paper maps took lead in “Super price” (2.16:1), “SMART” (3.13:1), “Professional seller” (8.51:1), “Super Seller” (2.16:1), and “Product variants” (1.95:1) offers. The synthetic comparison was provided through empirical probability function named Auction Vignette Factor Synthetic index (AVFS). The AVFS indexes showed greater maturity in factor utilization of paper maps, while digital maps relied on basic type of auction factor i.e.: Buy-It-Now auction. AVFS empirical probability function revealed that over 67% of digital map auctions used only one auction vignette factor while for paper maps it was 19%. Paper maps auctions were managed by the sellers in different way i.e., over 73% of auctions had two or three factors presented in the auction. The novelty of the paper is the number of factors taken into analysis and creation of Auction Vignette Factor Synthetic index (AVFS) with its empirical probability function representation.
Keywords: E-Commerce Auction; Maps; Auction Vignette; Auction Vignette Factors.